I am not sure but I think the answer is of second one.
Answer:
f(x) = |x + 1| + 1
Step-by-step explanation:
A reflection over the y-axis followed by a reflection over x-axis is equivalent to a reflection about origin.
f(x) = -|x-1| -1
reflection over the x-axis:
-f(x) = (-1)*(-|x-1| -1) = |x-1| +1
reflection over the y-axis of the previous function:
-f(-x) = |-x-1| +1 = |x + 1| + 1
which is the reflection of f(x) about the origin
$3 because you can not round this up to $4 because the order to rounder up you need to have more than $.50